Oncoplastic reduction mammoplasty for breast cancer in women with macromastia: long term aesthetic, functional and satisfaction outcomes - Emiroglu, Mustafa; Karaali, Cem; Salimoglu, Semra; Sert, Ismail; Aydin, Cengiz (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Despite the increase in studies concerning oncoplastic reduction mammoplasty (ORM), data showing long-term aesthetic and patient satisfaction for ORM in patients with macromastia remain limited. Therefore, this study evaluated the long-term results of tumorectomy and concomitant bilateral ORM for early-stage breast cancer patients with macromastia in terms of cosmesis, patient satisfaction, and functional outcomes. Material and methods : Retrospective data of patients with macromastia undergoing ORM for breast cancer between 1996 and 2011 were examined and evaluated regarding the aesthetic results, patient satisfaction, and functional outcomes. Results : The median age of the 82 patients was 50 years. The median follow-up was 120 months (range: 28–212 months). The median breast volume was 1402 cm 3 , and the median weight of the excised breast material was 679 g. A good or excellent evaluation of the cosmetic outcome was as follows: self-evaluation: 84.1% at the early-stage, 80.3% at the later stage; panel evaluation: 75.4% at the late-stage. Median patient satisfaction rates were 9.1% for early-stage disease and 8.8% for late-stage disease. Reduced mobility and intertrigo improved by three-fold during the post-operative period. Conclusions : ORM for early-stage breast cancer in women with macromastia results in good cosmesis in both the early-stage and long-term, and is quite acceptable for use in patients. Patients reacted favorably to the prospect of having their breast cancer and macromastia treated in a single session, and positive results continued over the long-term.